CALCULATION OF THE STRESS-STRAIN STATE OF CYLINDRICAL SHELLS INTERACTING WITH THE SOIL - S. Yakubov; E. Pirimkulov; N. Allamurodova; G.Tuganov (Journal of Higher Education and Academic Advancement, 2024)
The work deals with issues related to calculations with the calculation of the stress-strain state of circular cylindrical shells interacting with the soil. The results of calculating the distribution of soil pressure along the perimeter of pipelines are presented